Internet connectivity disruption in Italy (Italy) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Italy. Data sourced from IODA.
Network Disruption Incident ID: IT-2026-0017. Severity: critical. Confidence: 67%